Issues of Improving the Role of the Prosecutor's Office in Public Administration and the Legal Basis of its Activities (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes the role of the prosecutor's office in the system of separation of powers and legislative norms related to the improvement of its organizational and legal aspects. Conclusions and proposals on existing problems in national legislation and their elimination were put forward on the role of the prosecutor's office in the state mechanism and on some aspects of improving the organizational and legal foundations of the activities of this body.